Pengaruh Leverage dan Ukuran Perusahaan Terhadap Profitabilitas (Studi Empiris Pada Perusahaan Properti dan Real Estate Yang Terdaftar di BEI Tahun 2009-2012) - Rirind Lahmi Febria; Halmawati Halmawati (Universitas Negeri Padang, 2014)
This study aimed to examine: 1) the effect of leverage on profitability 2) effect of firm size on profitability. This research study considered causative. The population was proverty and real estate companies listed on the Indonesia Stock Exchange in 2009 until 2012. The research sample was determined by the method of purposive sampling to obtain a sample of 30 companies. Types of data used are secondary data and methods of analysis used is multiple regression. This study concluded that leverage was significantly influence profitability, 2) Firm size is not significantly influence the profitability. In this study suggested that further research should consider expanding the sample beyond the properti and real estate sector and extend the observation period, so that the results obtained can be generalized. And also the number of other factors that need to be considered profitability by further research. Subsequent researchers can conduct research associated with profitability, using a variety of relevant variables, which certainly influenced on the performance and development of the profitability of a companyKeywords : leverage,firm size, profitability